Inelastic Compaction in High‐Porosity Limestone Monitored Using Acoustic Emissions. Issue 12 (29th December 2017) - Baud, Patrick; Schubnel, Alexandre; Heap, Michael; Rolland, Alexandra
Abstract: We performed a systematic investigation of mechanical compaction and strain localization in Saint‐Maximin limestone, a quartz‐rich, high‐porosity (37%) limestone from France. Our new data show that the presence of a significant proportion of secondary mineral (i.e., quartz) did not impact the mechanical strength of the limestone in both the brittle faulting and cataclastic flow regimes, but that the presence of water exerted a significant weakening effect. In contrast to previously published studies on deformation in limestones, inelastic compaction in Saint‐Maximin limestone was accompanied by abundant acoustic emission (AE) activity. The location of AE hypocenters during triaxial experiments revealed the presence of compaction localization. Two failure modes were identified in agreement with microstructural analysis and X‐ray computed tomography imaging: compactive shear bands developed at low confinement and complex diffuse compaction bands formed at higher confinement. Microstructural observations on deformed samples suggest that the recorded AE activity associated with inelastic compaction, unusual for a porous limestone, could have been due to microcracking at the quartz grain interfaces. Similar to published data on high‐porosity macroporous limestones, the crushing of calcite grains was the dominant micromechanism of inelastic compaction in Saint‐Maximin limestone. New P wave velocity data show that the effect of microcracking was dominant near the yield point and resulted in a decrease in P wave velocity, while porosity reduction resulted in a significant increase in P wave velocity beyond a few percent of plastic volumetric strain. These new data highlight the complex interplay between mineralogy, rock microstructure, and strain localization in porous rocks. Key Points: Presence of significant quartz (20 wt. %) did not impact the mechanical behavior of Saint‐Maximin limestone (porosity 37%) Inelastic compaction in Saint‐Maximin limestone was accompanied by abundant acoustic emission (AE) activity, capturing strain localization Microcracking reduced P wave velocity near the yield point, while porosity reduction resulted in a significant increase in P wave velocity